LINC00461 SNPs rs933647 and rs201864123 modify the risk of adenoid hypertrophy susceptibility for children in South China - Hou, Chao; Luo, Xilian; Wan, Xin; Chen, Kaining; Xian, Zhongren; Xu, Kaixiong; Zeng, Yingjia; Wang, Chenlu; Yang, Wan; Zheng, Zilin; Lin, Yueling; Lu, Zhaojin; et al. (Frontiers in Genetics, 2025)
BackgroundAdenoidal hypertrophy (AH) is commonly observed in childhood and closely linked to obstructive sleep apnea (OSA). Despite the high prevalence of AH, its pathophysiological mechanisms remain incompletely understood. We attempt to explore this issue from a genetic perspective. Elevated levels of LINC00461 have been identified in OSA tissues. We aimed to explore the relationship between susceptibility to adenoid hypertrophy and LINC00461 gene polymorphisms.MethodsWe genotyped the LINC00461 single nucleotide polymorphisms (SNPs) rs933647 and rs201864123 in 546 AH patients and 574 healthy controls. Odds ratios (ORs) and 95% confidence intervals (CIs) were calculated to assess the association between the SNPs and AH risk. The SIPI (Susceptible-Infected-Protected-Infected) method was utilized to analyze SNP-SNP interactions between rs933647 and rs201864123.ResultsOur study found that the rs933647 GA polymorphism was associated with an increased risk of AH. Similarly, the T allele of SNP rs201864123 increased AH risk in southern Chinese children. Furthermore, SIPI analysis demonstrated an interaction between these SNPs associated with adenoid hypertrophy risk.ConclusionThe LINC00461 rs933647 GA genotype and rs201864123 T variant may contribute to the susceptibility of AH in the child population of China.